High‐Resolution Imaging of Human Viruses in Liquid Droplets (Adv. Mater. 37/2021). Issue 37 (14th September 2021) - Jonaid, GM; Dearnaley, William J.; Casasanta, Michael A.; Kaylor, Liam; Berry, Samantha; Dukes, Madeline J.; Spilman, Michael S.; Gray, Jennifer L.; Kelly, Deborah F.
Abstract : High‐Resolution Imaging High‐resolution structures of human viruses in liquid droplets are determined using rapid data collection procedures adapted from cryo‐electron‐microscopy. In article number 2103221, Deborah F. Kelly and co‐workers report real‐time imaging strategies to visualize atomic details of virus vehicles used in gene‐delivery and the treatment of COVID‐19. Design credit: Daryl Branford, Director of Science‐Art Initiatives, Huck Institutes of the Life Sciences, Penn State University.